2023
DOI: 10.1371/journal.pgph.0002173
|View full text |Cite
|
Sign up to set email alerts
|

Transitions from hospital to home: A mixed methods study to evaluate pediatric discharges in Uganda

Olive Kabajaasi,
Jessica Trawin,
Brooklyn Derksen
et al.

Abstract: The World Health Organization (WHO) Integrated Management of Childhood Illness (IMCI) guidelines recognize the importance of discharge planning to ensure continuation of care at home and appropriate follow-up. However, insufficient attention has been paid to post discharge planning in many hospitals contributing to poor implementation. To understand the reasons for suboptimal discharge, we evaluated the pediatric discharge process from hospital admission through the transition to care within the community in U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“… 31 Previous studies have reported that a well-implemented discharge policy has the potential to improve the hospital discharge process. 32 However, our study found that no policy or guideline has been put in place at MRRH to be followed by healthcare providers during discharge and this calls for the hospital leadership’s prompt action to institute such discharge planning policies.…”
Section: Discussionmentioning
confidence: 79%
“… 31 Previous studies have reported that a well-implemented discharge policy has the potential to improve the hospital discharge process. 32 However, our study found that no policy or guideline has been put in place at MRRH to be followed by healthcare providers during discharge and this calls for the hospital leadership’s prompt action to institute such discharge planning policies.…”
Section: Discussionmentioning
confidence: 79%
“…Without an effective intervention, risk prediction has limited utility. Understanding discharge as a dynamic process encompassing the time between admission and re-integration into community care is integral to our focus on admission factors [ 30 ]. Early identification allows post-discharge risk to be incorporated into discharge planning from the outset.…”
Section: Discussionmentioning
confidence: 99%
“…Early identification allows post-discharge risk to be incorporated into discharge planning from the outset. Significant challenges in preparing caregivers for discharge and the transition home have been identified, suggesting that early planning is an essential component of effective peri-discharge care [ 30 ].…”
Section: Discussionmentioning
confidence: 99%